Between worlds : a sourcebook of central European avant-gardes, 1910-1930 - Benson, Timothy O. (Los Angeles : Los Angeles Country Museum of Art ; Cambridge, Ma. : The MIT Press, 2002)
The avant-garde movements of Central Europe were an integral part of modernism's evolution as it reached its peak throughout the continent during the 1920s. Written documents―manifestoes, artists' statements, and reviews―were the lifeblood of these movements and, during the periods when political events conspired to isolate them, one of their few means of communication and exchange. Much of this crucial evidence has become lost to us, and the artistic avant-gardes of Central Europe have been a blind spot of modernist studies. Until their narratives have been recovered, the story of modernism will remain incomplete. In this book an international team of scholars has selected an essential compendium of documents that take an important step toward regaining this lost perspective. Between Worlds contains primary documents of the avant-gardes in Austria, the Czech lands, Germany, Hungary, Poland, Romania, and Yugoslavia from 1910 to 1930. The manifestoes and magazines of Western European radical art circles are well known to Western scholars, but few have researched the pages of magazines such as Zenit, Integral, Punct, 75 HP, Tank, and Ma. We know about Italian Futurism but not about Polish Futurism. Few Westerners are aware that French surrealist magazines drew much of their inspiration from Czech publications. The hundreds of documents in the book, almost all of them translated into English for the first time, bring back into circulation landmark texts by the major writers, editors, artists, magazines, and movements of Central Europe. With this publication they are restored to their rightful place in the pantheon of modernism. Between Worlds is distributed for the Los Angeles County Museum of Art.
Keywords: avangarda; Središnja Europa; avangarde Središnje Europe; umjetnost